EFFECTIVTENESSS OF SPEED DEPENDENT TREADMILL TRAINING VERSUS CONVENTIONAL TRAINING TO IMPROVE GAIT VELOCITY FOR HEMI PARETIC PATIENTS - .T, Murugaraj; .M, Srinivasan; N, Sabarish Hariharan.; .E, Shanmugananth (International Journal of Psychosocial Rehabilitation, 2021)
Background: Stroke is the disease that affects the arteries leading to and within the brain. It is the number 5th reason for death and a leading cause of impairment all over the world. Stroke happens over the blood vessels that convey the oxygen and supplements to the cerebrum is either hindered by clump or blasts. The incidence of stroke affects approximately 6, 00,000 individuals each year with the estimated number of 4, 00,000 stoke survivors. In this study an attempt is made to enumerate the gait velocity in hemiparetic stroke patients. Objective: The object of the study is to know the difference between effectiveness of speed dependent treadmill training versus conventional training to improve gait velocity for hemiparetic patients. Methods: The study was done in physiotherapy department, MGMCRI where the patient was referred from neurology department. A sum of 30 samples was selected from the population using convenient sampling method. All the 30 samples were divided into 2 groups consisting of 15 members each. The gait velocity was recorded using the stopwatch on both group prior to the training program is the pretest measurement was taken. Experimental group received speed dependent treadmill training. The conventional walking training 4 sessions per week for 4-week duration. The post test results were recorded and documented. The population was selected based on the inclusion criteria. Patients with cognitive deficit, orthopedic disorders, unstable cardiovascular patients and unco-operated patients were eliminated from this study. Result: the result of the study makes us conclude that sped dependent treadmill training is much effective in improving the gait velocity then the conventional walking training